STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN KUALITAS OUTPUT SISWA DI SMK - Arkan, Fa'iq; Aminuddin Aziz, Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of student outcomes in vocational education is an important indicator of the success of educational institutions in preparing graduates with adequate competencies to meet workforce demands. The improvement of student outcomes is determined not only by the learning process but also by the effectiveness of human resource management (HRM), which includes both educators and educational staff. This study aims to describe HRM strategies, student outcome quality, and the role of HRM strategies in improving student outcomes at SMK Tamansiswa Mojoagung Jombang. A qualitative approach with a case study design was employed. The research subjects included the principal, teachers, educational staff, and students. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings indicate that HRM strategies are implemented through planning educator staffing needs, competency-based recruitment and selection, and professional development through In-House Training (IHT), supervision, and performance evaluation, as well as compensation and rewards for high-performing educators. These strategies contribute to improving student outcomes, reflected in vocational skills, discipline, work readiness, adaptability, and high graduate absorption in the workforce. The study concludes that well-planned and sustainable HRM strategies play a crucial role in enhancing graduate quality and employability.